Recognition Method of Mine Water Sources Based on Factor Analysis - Li Yue; Shi Longqing (Global Journal of Earth Science and Engineering, 2020)
Taking Jiaozuo mining area as the research background, according to the survey of water samples among the main water-filled aquifers of the mine and water gushing sources due to the exploitation of the No.21 coal seams in Shanxi group, six kinds of water chemical composition were selected as the sample indexes, including Cl-, SO42-, HCO3-, Na++K+, Ca2+, Mg2+, based on the data of groundwater chemical composition, and a principal component analysis was applied to establish the mathematical model by the method of factor analysis. A piper diagram was used to intuitively conduct the synthetical analyses for the general chemical characteristics and water quality types of the water samples. At the same time, via the comparative analysis between the water properties of water exits and that of the main aquifers in the Jiaozuo mining area, discrimination of the hybridization of the multiple water gushing sources due to coal mining was done. Moreover, by dint of the SPSS factor analysis, the water chemical proxies were carried on dimensionality reduction from the six kinds of water chemical composition to the three major factors, which replaced the original variables to participate in the data modeling. The results of the study showed that the combination of the piper diagram and the factor analysis modeling could effectively identify the water gushing sources owing to exploiting the No.21 coal seams of the Shanxi group in the Jiaozuo mining area and rank on the basis of the contributions of each aquifer to the amounts of water bursting in the mine, solving the problems of information superposition and correlations consisted in the identification of water gushing sources, which provides a theoretical basis for the prevention and cure of the mine water disasters.